2015
DOI: 10.1038/srep11809
|View full text |Cite
|
Sign up to set email alerts
|

Effect of N-n-butyl haloperidol iodide on ROS/JNK/Egr-1 signaling in H9c2 cells after hypoxia/reoxygenation

Abstract: Reactive oxygen species (ROS)-induced oxidative stress in cells is an important pathophysiological process during myocardial ischemia/reperfusion (I/R) injury, and the transcription factor Egr-1 is a master switch for various damage pathways during reperfusion injury. An in vitro model of myocardial I/R injury and H9c2 cardiomyoblast cells hypoxia/reoxygenation (H/R) was used to assess whether there is abnormal intracellular ROS/JNK/Egr-1 signaling. We also assessed whether N-n-butyl haloperidol (F2), which ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 33 publications
1
32
0
Order By: Relevance
“…Our former investigations have shown that the cardioprotection of F 2 may be linked to its capacity block calcium channels [20–22] and inhibition of the overexpression of early growth response gene-1, a major switch for multiple pathways of reperfusion injury [2325]. Consistent with the attenuation of myocardial injury, we have also demonstrated that F 2 inhibits H/R-induced ROS generation in cardiomyocytes [26]. However, related studies of F 2 on cultured CMECs in vitro are limited.…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…Our former investigations have shown that the cardioprotection of F 2 may be linked to its capacity block calcium channels [20–22] and inhibition of the overexpression of early growth response gene-1, a major switch for multiple pathways of reperfusion injury [2325]. Consistent with the attenuation of myocardial injury, we have also demonstrated that F 2 inhibits H/R-induced ROS generation in cardiomyocytes [26]. However, related studies of F 2 on cultured CMECs in vitro are limited.…”
Section: Introductionsupporting
confidence: 68%
“…The Increased ROS levels in the vasculature results in endothelial damage [37], which acts as the major etiological factor underlying I/R injury [38]. We showed in our former study that F 2 reduces the production of ROS after H/R in cardiomyocytes, which is accompanied by improved myocardial function [26]. Consistent with these findings, our present data demonstrated that F 2 dose-dependently suppresses the generation of ROS in H/R-challenged CMECs.…”
Section: Discussionmentioning
confidence: 99%
“…31 A recent report revealed a convincing correlation between ROS and EGR1 expression and showed that intracellular ROS levels up-regulate EGR1 expression, and those researchers considered that EGR1 might act as the "damage hub" to mediate oxidative stress and the related ROS-induced damage during ischemia and reperfusion. 32 It has been established that the increase in ROS-induced damage during aging plays a vital role in ovarian aging. 33 The present study showed that EGR1 plays a role in promoting apoptosis in GCs under H 2 O 2 stimulation.…”
Section: Up-regulation Of Egr1 Induces P53 But Not Pten Activationmentioning
confidence: 99%
“…However, conventional hypoxic cell culture devices, including a modular chamber or a gas incubator, must be opened again after hypoxic conditions have been established for experimental manipulations, such as confluency check, medium replacement and cytokine solution infusion [2]. Hypoxic cells eventually undergo reoxygenation when the culture dish is exposed to the normoxia atmosphere, resulting in reactive oxygen species generation and cell damage [3,4]. A glove box allows the manipulation of the culture dish without exposing it to the atmosphere, but it is very expensive and large; hence, it is often not available in small-scale laboratories [2].…”
mentioning
confidence: 99%